Seasonal variation characteristics of water quality in the Sunxi River Watershed, Three Gorges Reservoir Area - Hou, Wenning; Wang, Haiyan; Zheng, Yonglin; Wang, Yige; Yang, Dandan; Meng, Hai (PeerJ (San Francisco, CA), 2022)
The seasonal change characteristics of water quality in the Sunxi River watershed, which is a typical watershed in the tail area of the Three Gorges Reservoir Area, must be studied to provide remediation ideas and specific measures for agricultural nonpoint source pollution in the reservoir area. A two-way repeated measures ANOVA was used to analyze the variation characteristics of chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP) concentrations in the upstream and downstream of the Sunxi River watershed in spring, summer, and autumn of 2018–2021. With data from autumn 2018 taken as an example, path analysis was applied to study the effect degree of influencing factors on TN concentrations. The two-way repeated measures ANOVA illustrated that the COD, TN, and TP concentrations in the downstream were significantly higher than those in the upstream ( P < 0.05). In addition, the COD concentrations were the highest in summer 2019, followed by spring of 2019 and 2021, and TN and TP concentrations were higher in spring and summer. The TN and TP concentrations were comparatively lower in the autumn. The path analysis showed that electrical conductance and dissolved oxygen directly affected the TN concentrations, and water temperature mainly affected the TN concentrations via the indirect effects of electrical conductance and dissolved oxygen. The water quality of upstream Sunxi River watershed was better than that of downstream, and the water quality in autumn was better than spring and summer in 2018–2021. For water quality management and ecological restoration of the Sunxi River watershed, further attention should be paid to the water quality changes in the downstream and in spring and summer and to the impact of water temperature, electrical conductivity, and dissolved oxygen on the water quality.